A review on the potential use of natural products in overweight and obesity. (28th February 2022) - Li, Xin; Zhang, Yu; Wang, Shuxuan; Shi, Caihong; Wang, Shuang; Wang, Xin; Lü, Xin
Abstract: With the increase in unhealthy lifestyles, obesity is increasingly common, which could cause many metabolic diseases. In recent research, natural product extracts have shown tremendous potential antiobesity effects via different mechanisms. In this review, we focused on widely adopted extraction methods, bioactive ingredients types, and antiobesity mechanisms of natural product extracts in the recent reports. The extraction methods include solid–liquid extraction, microwave‐assisted extractions, and supercritical fluid extraction. Moreover, the bioactive ingredients identified in natural product extracts are phenolic compounds, oligosaccharides, polysaccharides, and terpenoids. These exert antiobesity effects through multiple mechanisms, including suppressing the appetite, increasing energy expenditure, inhibiting enzyme activity, modulating lipid homeostasis and adipocyte lifecycle, reducing oxidative and inflammation, and improving intestinal bacteria. However, the antiobesity effects of natural products require further evaluation. Furthermore, the improvement of the bioavailability and effective and safe human dose of these bioactive ingredients should be the focus of future work.